Pembelajaran dan Implementasi Etika Bisnis Islam: Studi pada Mahasiswa Akuntansi Syariah IAIN Surakarta - Galuh Anggraeny (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This study aims to explore the practice of learning Islamic business ethics and its implementation among the sharia accounting students of IAIN Surakarta. With a qualitative approach, the results show that the practice of learning Islamic business ethics can be well received by the students. Islamic business ethics has also been applied in business practices by students, such as avoiding prohibited transactions, not reducing scales, and not taking too high a profit. The interviewees also realize the importance of ethics in business, therefore Islamic business ethics needs to be socialized to the wider community, so Islamic business ethics can be implemented in all business activities. Thus, the implementation of Islamic business ethics still needs to be expanded again, involving all levels of society, not only students and academics.Keywords: Islamic business ethics, learning, implementation